Herbivory enhances the effect of environmental variability on plant community composition and beta diversity. (24th April 2020) - Brambila, Alejandro; Chesnut, John W.; Prugh, Laura R.; Hallett, Lauren M.
Abstract: Aim: Understanding the factors that shape biodiversity over space and time is a central question in ecology. Spatiotemporal environmental variation in resource availability can favor different species, generating beta diversity patterns that increase overall diversity. A key question is the degree to which biotic processes—in particular herbivory—enhance or dampen the effect of environmental variation on resource availability at different scales. Location: We tested this question in a semi‐arid California grassland, which is characterized by high rainfall variability. The system supports giant kangaroo rats ( Dipodomys ingens ), which form mounds that structure spatial variability in soil nutrient availability. Methods: From 2008 to 2017 we implemented a cattle herbivory exclusion experiment to test whether herbivory moderates the effect of spatial and inter‐annual resource variability on plant biomass and diversity both on and off mounds. Results: Grazing reduced local diversity regardless of mound status or amount of precipitation. However, we found that plant productivity was higher on than off mounds, increased following high rainfall years, and that grazing increased these on‐ versus off‐mound differences in wet years—especially after a major drought. Correspondingly, grazing led to on‐mound communities that were more different from each other and from off‐mound communities. Conclusions: Taken together, our results suggest that herbivory generally enhances habitat heterogeneity across this arid landscape, but is resource context‐dependent with greater effects seen in wetter years. Abstract : What effect does cattle grazing have in a spatiotemporally variable semi‐arid California grassland? We tested whether herbivory moderates the effect of resource variability (precipitation and rodent soil mounds) on plant biomass and diversity. Grazing reduced local diversity, but enhanced productivity differences, especially in wet years. Grazing also generated on‐mound communities that were more dispersed than off‐mound communities, enhancing habitat heterogeneity.